Welfare Transformation Through Productive Business Empowerment: A Review of Khadijah 2 Orphanage Surabaya - Sudarso, Satrio (International Journal of Management Science and Information Technology, 2024)
A study conducted at Khadijah 2 Orphanage in Surabaya shows how important an empowerment program is for orphans and destitute children. The aim of the program is to teach these children entrepreneurial skills through activities such as managing a business and marketing the orphanage's property. This empowerment method involves increasing knowledge and skills as well as participation in the management of the business. The results show that the children are more aware of the importance of entrepreneurship, especially through ventures, visits, and discussions that encourage them to do so. In addition, their interactions with prospective tenants generated new knowledge about property management and marketing, which enabled them to learn to communicate well and provide satisfactory services to tenants. The orphans continue to learn and change their marketing strategies. Not only do they acquire skills through this program; but it also gives them the opportunity to develop and contribute to their environment, paving the way to a better and more independent future. This shows that there is significant support in helping orphans and dhu'afa children prepare themselves for a better future.